Sechs Duette Flauto II op. 75 fur zwei Floten Nr. 1-3 KV.156 (W.Barge) Nr. 4-6 KV.157 (Emil Wehsener)(1-17), (1-17) - MOZART, Wolfgang Amadeus (Zimmermann)
Sechs Duette Flauto II op. 75 fur zwei Floten Nr. 1-3 KV.156 (W.Barge) Nr. 4-6 KV.157 (Emil Wehsener)